Killing two birds with one stone: trans-kingdom suppression of PAMP/MAMP-induced immunity by T3E from enteropathogenic bacteria - Fraiture, Malou; Brunner, Frédéric (Frontiers in Microbiology, 2014)
Within the past decade, remarkable similarities between the molecular organization of animal and plant systems for non-self discrimination were revealed. Obvious parallels exist between the molecular structures of the receptors mediating the recognition of pathogen- or microbe-associated molecular patterns (PAMPs/MAMPs) with plant pattern recognition receptors (PRRs) strikingly resembling mammalian Toll-like receptors. Mitogen-activated protein (MAP) kinase cascades, leading to the transcriptional activation of immunity-associated genes, illustrate the conservation of whole molecular building blocks of PAMP/MAMP-induced signaling. Enteropathogenic Salmonella and Escherichia coli use a type three secretion system (T3SS) to inject effector proteins into the mammalian host cell to subvert defense mechanisms and promote gut infection. Lately, disease occurrence was increasingly associated with bacteria-contaminated fruits and vegetables and common themes have emerged with regard to whether and how effectors target innate immune responses in a trans-kingdom manner. We propose that numerous Salmonella or E. coli effectors may be active in planta and tend to target central components (hubs) of immune signaling pathways.